Material distributive topology design of UWB antenna using parallel computation of improved BPSO with FDTD. Issue 2 (8th November 2018) - Thilaga Shri Chandra, A. P.; Senthilkumar, L.; Meenakshi, M.
Abstract: In this article, the material distributive topology-based design optimization of ultra-wide band (UWB) antenna is proposed by using improved binary particle swarm optimization (BPSO) with finite difference time domain (FDTD) method. In the improved BPSO implementation, the velocity of each particle is calculated based on complete set of bits of particle position vector. The V-shaped transfer function is employed to transform all real values of velocities to values in the interval [0, 1]. The fitness function of all the particles in BPSO algorithm are computed parallely by using FDTD simulation. The usage of FDTD and the parallel computation helps in analyzing the broadband frequency characteristics of the antenna with a single simulation run. The return loss of the optimized UWB antenna obtained from FDTD, Computer Simulation Technology (CST) simulation and practical measurement are in good agreement and show good impedance matching.